Public workers in service of America : a reader - Gooding, Frederick W., Jr; Yellin, Eric Steven, 1978-; McCartin, Joseph Anthony; Boris, Eileen, 1948- (Working class in American history., 2023)
"From white-collar executives to mail carriers, public workers meet the needs of the entire nation. Frederick W. Gooding Jr. and Eric S. Yellin edit a collection of new research on this understudied workforce. Part One begins in the late nineteenth- and early twentieth century to explore how questions of race, class, and gender shaped public workers, their workplaces, and their place in American democracy. In Part Two, essayists examine race and gender discrimination while revealing the subtle contemporary forms of marginalization that keep Black men and Black and white women underpaid and overlooked for promotion. The historic labor actions detailed in Part Three illuminate how city employees organized not only for better pay and working conditions but to seek recognition from city officials, the public, and the national labor movement. Part Four focuses on nurses and teachers to address the thorny question of whether certain groups deserve premium pay for their irreplaceable work and sacrifices or if serving the greater good is a reward unto itself. Contributors: Eileen Boris, Cathleen D. Cahill, Frederick W. Gooding Jr., William P. Jones, Francis Ryan, Jon Shelton, Joseph E. Slater, Katherine Turk, Eric S. Yellin, and Amy Zanoni"--